Host Factors and HIV-1 Replication: Clinical Evidence and Potential Therapeutic Approaches - Santa-Marta, Mariana; Brito, Paula; Godinho-Santos, Ana; Goncalves, Joao (Frontiers in Immunology, 2013)
HIV and human defense mechanisms have co-evolved to counteract each other. In the process of infection, HIV takes advantage of cellular machinery and blocks the action of the host restriction factors. A small subset of HIV+ individuals control HIV infection and progression to AIDS in the absence of treatment. These individuals known, as long-term non-progressors (LNTPs) exhibit genetic and immunological characteristics that confer upon them an efficient resistance to infection and/or disease progression. The identification of some of these host factors led to the development of therapeutic approaches that attempted to mimic the natural control of HIV infection. Some of these approaches are currently being tested in clinical trials. While there are many genes which carry mutations and polymorphisms associated with non-progression, this review will be specifically focused on HIV host restriction factors (RF) including both the main chemokine receptors and chemokines as well as intracellular restriction factors including, APOBEC, TRIM, tetherin and SAMHD1. The understanding of molecular profiles and mechanisms present in LTNPs should provide new insights to control HIV infection and contribute to the development of novel therapies against AIDS.